Squamous cell carcinoma complicating a chronic lesion of hidradenitis suppurativa: a case report and review of the literature. Issue 2 (29th September 2016) - Jourabchi, Natanel; Fischer, Alexander H; Cimino‐Mathews, Ashley; Waters, Kevin M; Okoye, Ginette A
Abstract: Squamous cell carcinoma (SCC) arising from chronic hidradenitis suppurativa (HS) is rare; however, the morbidity associated with this presentation is high and management has not been standardised or optimised. We present a case of HS of the perineum and buttocks complicated by SCC, requiring multiple extensive surgical resections. Adjuvant radiotherapy was withheld initially because of concern for poor healing of the surgical wound but was eventually initiated after a second recurrence was identified. The patient ultimately expired 4 years after the initial diagnosis of SCC. We also review 80 cases of SCC complicating HS found in the English literature. Case reports and mechanistic studies suggest the possibility that human papilloma virus and smoking may be risk factors associated with SCC in HS. Despite the majority of SCC cases being well‐differentiated tumours in HS, the highly aggressive nature of SCC in HS and its high likelihood for rapid progression, recurrence, metastasis and high mortality suggests the need to advocate for aggressive treatment. We recommend an aggressive approach to management at the time of SCC diagnosis in HS, which includes appropriate imaging to establish the extent of the tumour, large and deep surgical excision, sentinel lymph node evaluation, consultation with radiation oncology for potential adjuvant radiation therapy and close surveillance.